Engaging youth as leaders and partners can improve substance use prevention: a call to action to support youth engagement practice and research - Parissa J. Ballard; Heather K. Kennedy; Jessica J. Collura; Elena Vidrascu; Chelsey Garcia Torres (Substance Abuse Treatment, Prevention, and Policy, 2023)
Abstract Background As a subfield of prevention science, substance use prevention researchers and professionals are increasingly focused on translating research into practice, developing the workforce of prevention specialists, and creating a robust prevention infrastructure. One critical need for professional development among the substance use prevention workforce is training and technical assistance around how to include young people in developing, implementing, and evaluating substance use prevention programs. Main body Amplifying youth voices can increase the quality and responsiveness of youth prevention research and practice, as well as hasten and improve the translation of prevention interventions into practice while also benefiting youth themselves. Yet, youth engagement is multi-layered and nuanced. Training prevention professionals who work with youth in youth development and youth/adult partnerships is critical to support meaningful youth engagement efforts. We assert that the substance use prevention workforce needs at least three specific competencies to engage youth meaningfully in prevention: 1) understand adolescent development and the core elements of youth-adult partnerships; 2) apply this knowledge to program design and practice; and 3) implement relational practices to share power with young people. Conclusion Incorporating the insights of young people can improve substance use prevention. The substance use prevention workforce should be supported in developing competencies to meaningfully engage youth. These competencies require training, and resources must be devoted to support appropriate training.